Antifungal activities of Chaetomium spp. against Fusarium wilt of tea - Nguyen Huu Phong; Wattanachai Pongnak; Kasem Soytong (My University, 2016)
An isolate of Fusarium denominated as NHP-Fusa-2 from tea wilt and root-rot diseased sample collected in Vietnam was identified as Fusarium oxysporum based on molecular analysis of translation elongation factor-1α sequence. Interestingly, it is the first time F. oxysporum is reported as a causal pathogen of wilt and root-rot disease of tea in Vietnam. Chaetomium spp. were investigated to control F. oxysporum NHP-Fusa-2 in in vitro test. Three antagonists (Ch. cupreum CC3003, Ch. globosum CG05, and Ch. lucknowense CL01) inhibited mycelial growth by 31.69-34.03% and reduced conidial production of the pathogen by 67.25-75.92% in the bi-culture antagonistic test after 30 days with non-significant difference in their effect. All the crude extracts of these antagonists significantly inhibited mycelial growth and conidial production of NHP-Fusa-2. MeOH extract of CC3003 was more effective in conidial inhibition of the pathogen than the others, the effective dose (ED50) was 85.30 μg/ml of which, it was hexane (49.32 μg/ml) and EtOAc extract (62.17 μg/ml) in the case of CG05 and CL01, respectively.
Keywords: Wilt disease; Chaetomium; Chaetomium globosum; Root rot; Plant Pathogens and Fungal Diseases